Differences in perceived time duration and reading performance for static and moving text - Chow, Shirley Jia Shiuan (2016)
Moving stimuli is perceived to last for a longer time duration (Brown, 1995). This study examines whether this effect generalizes to perceiving words. To determine whether text motion influences reading behavior, participants were also asked to report spelling errors (part 1) and answer true/false comprehension questions (part 2). For the first part, a two factor within subjects design was adopted. Participants viewed individual sentences varying in terms of text movement and actual presentation duration. Then, they estimated the time duration of presentation and reported whether spelling errors were seen. Actual presentation duration, but not text movement, significantly influenced estimated time durations. Differences in overall incorrect responses for error detection across time duration and text movement conditions are non-significant. Decomposing incorrect responses into false positives and false negatives revealed that the number of false positives are significantly higher in static conditions, whereas the numbers of false negatives were significantly higher in moving conditions. For part 2, a single factor within subject design found that text movement did not significantly affect reading comprehension or estimated time durations. Overall, the data suggests that text movement does not cause time dilation, and that there is a bias towards reporting errors in static as compared to moving text conditions. Limitations and implications of our study are discussed.